2019
DOI: 10.3390/metabo10010017
|View full text |Cite
|
Sign up to set email alerts
|

Green and White Asparagus (Asparagus officinalis): A Source of Developmental, Chemical and Urinary Intrigue

Abstract: Asparagus (Asparagus officinalis) is one of the world’s top 20 vegetable crops. Both green and white shoots (spears) are produced; the latter being harvested before becoming exposed to light. The crop is grown in nearly all areas of the world, with the largest production regions being China, Western Europe, North America and Peru. Successful production demands high farmer input and specific environmental conditions and cultivation practices. Asparagus materials have also been used for centuries as herbal medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(110 citation statements)
references
References 118 publications
(221 reference statements)
0
74
1
1
Order By: Relevance
“…The edible portion of this herbaceous perennial is constituted by its spears or young stems produced by the underground crown, which may be green, green-purple, or purple when harvested above ground or white when purposely harvested before exposed to sunlight. Asparagus spears are considered a rich source of minerals [285], amino acids and dietary fibers [286], saponins [287,288], vitamins and volatile sulfur organic compounds [289], and especially of phenolic compounds and flavonoids [290], including anthocyanins that are responsible for the purple color of the bracts of green spears or of the whole spears in purple asparagus genotypes [23,154,291]. Being rich of all these bioactive compounds it is difficult to isolate the effect of anthocyanins and specific pigments, nevertheless several studies have demonstrated the antioxidant properties of anthocyanins in the species [284].…”
Section: Asparagusmentioning
confidence: 99%
“…The edible portion of this herbaceous perennial is constituted by its spears or young stems produced by the underground crown, which may be green, green-purple, or purple when harvested above ground or white when purposely harvested before exposed to sunlight. Asparagus spears are considered a rich source of minerals [285], amino acids and dietary fibers [286], saponins [287,288], vitamins and volatile sulfur organic compounds [289], and especially of phenolic compounds and flavonoids [290], including anthocyanins that are responsible for the purple color of the bracts of green spears or of the whole spears in purple asparagus genotypes [23,154,291]. Being rich of all these bioactive compounds it is difficult to isolate the effect of anthocyanins and specific pigments, nevertheless several studies have demonstrated the antioxidant properties of anthocyanins in the species [284].…”
Section: Asparagusmentioning
confidence: 99%
“…Asparagus officinalis (ASP) is a perennial vegetable with remarkable anti-fungal, anti-hepatotoxic, cytotoxic, antimutagenic, anti-inflammatory and diuretic properties (6). The roots and buds of ASP are rich in many bioactive phytochemicals including oligosaccharides, steroidal saponins, amino acid derivatives and essential minerals, which has been used for treatment of various chronic inflammation diseases and cancers in Chinese traditional medicine (6)(7)(8). Polysaccharides, steroidal saponins and flavonoids extracted from ASP have been reported as main bioactive constituents that might have anti-tumor properties (9).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature review conducted, no study indicating that asparagus prevents carbohydrate damage was found. Considering the mineral content of asparagus (Pegiou et al, 2020;Guo, et al, 2020), the low Na content of this wild plant suggests that this plant can be used as an important food source for blood pressure patients (Table 3). Wild asparagus plant is rich in terms of potassium, calcium, magnesium and phosphorus content.…”
Section: Conclusion Conclusion and Discussionmentioning
confidence: 99%